Data security protection schema of telecom operators under the environment of big data - Shengli ZHOU; Bin CHEN; Lifa WU (Dianxin kexue)
With the popularity of big data and cloud computing technology,data of telecom operators collected is increa-singly larger,and much more various.The data faces the risk of broken security management,hacker attacks,and imper-fection of risk assessment,etc.The current situation of data security in the environment was analyzed,and a more com-plete data security implementation plan was put forward.From the two aspects of data security technology and manage-ment,several strategies were proposed,including security classification,privacy protection,data desensitization encryption and security protection.The proposed schema has been implemented in China Telecom data security protection project.